The influence of the Jigsaw type cooperative learning model on students' thinking abilities - anissa khairiyah; Laili Habibah Pasaribu; Lily Rohanita Hasibuan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This ponder points to analyze the impact of the jigsaw sort agreeable learning show on students' basic considering abilities, and see how colossal and positive or negative the impact that happens between the two factors. This investigate employments a quantitative approach strategy of genuine test sort. by utilizing the Pretest-Posttest Control Gather Plan investigate plan. The populace of this think about was all lesson VIII MTs Tarbiyah Islamiyah comprising of 2 classes totaling 55 understudies. The test utilized was lesson VIII-b as numerous as 30 understudies. the testing procedure utilized was arbitrary testing strategy. Information were collected through test questions on SPLDV fabric a few time as of late and after treatment of the jigsaw learning show. The information were analyzed utilizing parametric truthful tests, to be particular essential straight relapse tests with SPSS 22.0 The comes approximately of the examination appeared that the Sig.2 (2-tailed) esteem was 0.040 and 0.040 < 0.05, meaning that there was a noteworthy impact between variable X and variable Y, to be particular the impact of the jigsaw learning show on students' basic considering capacities.